Insertion of Metal‐Substituted Silylene into Naphthalene's Aromatic Ring and Subsequent Rearrangement for Silaspiro‐Benzocycloheptenyl and Cyclobutenosilaindan Derivatives. Issue 6 (10th December 2020) - Xu, Cheng; Ye, Zhen; Xiang, Li; Yang, Shuhan; Peng, Qian; Leng, Xuebing; Chen, Yaofeng
Abstract: Synthesis of silacycle compounds are of fundamental and application importance. Herein we report the first example of insertion of metal‐substituted silylene fragment into naphthalene's aromatic ring. More significantly, this insertion is followed by interesting rearrangements to yield silaspiro‐benzocycloheptenyl and cyclobutenosilaindan derivatives. The formation of cyclobutenosilaindan derivative includes the C−C bond cleavage and 4π electrocyclization steps; the formation of silaspiro‐benzocycloheptenyl derivative is more complicated, including the C−C bond cleavage, reversible 4π electrocyclization, C−H bond activation and C−Si bond cleavage. DFT investigations were carried out to shed light on the mechanistic aspects of these two rearrangements. The formed cyclobutenosilaindan potassium can readily react with PhOH, MeOTf, EtOTf, PhCH2 Cl or PhCOCl at room temperature to afford the hydrogen, alkyl, benzyl or benzoyl substituted cyclobutenosilaindans in high yields. Abstract : With naphthalene and (Me3 Si)3 CSiCl3 as the starting materials, silacyclopropanyl complexes of potassium and divalent ytterbium are synthesized, which can readily convert into silaspiro‐benzocycloheptenyl and cyclobutenosilaindan derivatives, showing the first example of insertion of a metal‐substituted silylene fragment into naphthalene's aromatic ring and rearrangements into the structurally intriguing silacycles.